P058 Demand for pre exposure prophylaxis for hiv (PREP) and the impact on clinical services: scottish men who have sex with men (MSM) perspectives. (8th June 2017) - Gilson, Rebecca; Clutterbuck, Daniel
Abstract : Introduction: Studies have assessed awareness and interest in taking PrEP but there is less data on ability and willingness to self-fund. Our aim was to assess how many eligible (high risk, PROUD study criteria) may want PrEP, how many ineligible (lower risk) MSM would be willing and able to self-fund and how PrEP may impact on risk taking behaviour. Methods: Self-completed anonymous questionnaire Questions included sexual risk and risk frequency, willingness to take PrEP, income, willingness to self fund and impact on risk taking. Results: Of 377 participants, 81.5% were aware of PrEP. 53 (15.5%) were eligible, of whom 50 (94.3%) aware of PrEP and 50 (94.3%) likely to want it. Of those ineligible, 229 (80%) aware of PrEP and 171 (60%) likely to want it. The majority of men reported they would not be more likely to have condomless sex or increase partner numbers. Discussion: Levels of awareness of PrEP in our population were much higher than the 30% previously reported in Scotland. Previous studies showed 50% would be willing to take PrEP. In this study, 94.3% of the 15.5% of men eligible and 60% of those ineligible were likely to want it. This will have implications for discussions and monitoring. A systematic review of PrEP 6 found no difference in condom use or numbers of partners. Our study indicates that men believe that risk taking behaviour will likely not increase.